Strategic learning and information and communication technology: a critical review - Carles Monerero Font; Antoni Badia Garganté (Ediciones Universidad de Salamanca, 2013)
<!--[if gte mso 9]> 0 0 1 93 514 USAL 4 1 606 14.0 <![endif]--> <!--[if gte mso 9]> Normal 0 21 false false false ES JA X-NONE <![endif]--><!--[if gte mso 9]> <w:LsdException Locked="false" P